A REVIEW OF HAZARDS AND PRECAUTIONARY MEASURES IN SCIENCE AND TECHNOLOGY LABORATORIES - Manal Rasheed Alonazi; Badria Eissa Alonazi; Nawal abdulaziz Maran Alonazi; Tardah Abdulaziz Marran Alanazi; Faleh Marzouq M Alyame; Tahani Saud Almutairi; Tariq Sulaiman B Alkazi; Abdullah Mubarak Muhammad; Salem hussain saban alyami; Saleh Obaid Almutairi; Maryam Abdullah Jaber Algaezani (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
While working in a science and technology laboratory, hazards are frequently encountered due to the usage of equipment, tools, and apparatus, or chemicals and reagents when conducting an experiment or research. Exposure to hazards occurs via different routes; inhalation, absorption, ingestion, and injection. This could lead to some detrimental health effects. Hazard prevention or minimization is a key factor in safety precaution. Aiming to create hazards and safety awareness, this review article provides the basic types of laboratory hazards (chemical, physical, and biological hazards) and safety measures to adopt as well as emergency response to hazards.